Physical Modelling of Geotechnical Structures in Ports and Offshore - Bałachowski Lech (Polish Maritime Research, 2017)
The physical modelling of subsoil behaviour and soil-structure interaction is essential for the proper design of offshore structures and port infrastructure. A brief introduction to such modelling of geoengineering problems is presented and some methods and experimental devices are described. The relationships between modelling scales are given. Some examples of penetration testing results in centrifuge and calibration chamber are presented. Prospects for physical modelling in geotechnics are also described.